Prevalence and associated factors of hypertension complications among hypertensive patients at University of Gondar Comprehensive Specialized Referral Hospital - Zemene Demelash Kifle; Meaza Adugna; Gashaw Sisay Chanie; Abdulwase Mohammed (Elsevier, 2022)
Background: Cardiovascular diseases (CVDs) were non-communicable diseases that remain the leading cause of disability and death in the world. Therefore, this study aimed to assess the prevalence and associated factors of hypertension complications among hypertensive patients at University of Gondar comprehensive specialized referral hospital. Method: A cross-sectional study was conducted to assess the prevalence and associated factors of hypertension complications, from 1st June 2020 to 30th August 2020. Interview-guided self-administered questionnaire and a chart review were used for data collection. Statistical significance was set at a 95% confidence interval using a P-value of ≤0.05 as a cutoff point. Results: Out of 428 hypertensive patients, 261 (61.0%) were males. They were from 19 to 84 years age group and the mean age of participants was 53.55 ± 16.65 years. Participants with a family history of hypertension were 5 times more likely to develop complications than those with no family history of hypertension (AOR = 5.372, 95% CI = 2.378, 12.134, p = 0.001). Participants who had sedentary physical activity were 4 times more likely to develop complications than those who had vigorous physical activity (AOR = 4.049, 95% CI = 1.463, 11.206, p = 0.007). Participants who had high waist circumference were 7 times (AOR = 7.229, 95% CI = 1.436, 36.394, p = 0.016) more likely to develop complications than those who had low waist circumference. Conclusion: In this study, being female, illiterate participants, having a family history of hypertension, doing sedentary exercise and obesity are factors associated with hypertension complications.